Tinjauan Yuridis terhadap Proses Eksekusi dalam Penyelesaian Sengketa Tanah di Indonesia - Hasan; Putri, Kattya Nusantari; Rezki Amalia; Sulaeman (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
"Execution is a crucial stage in civil law enforcement, particularly in land dispute resolution. Without execution, a court ruling holds only declarative legal value and lacks real binding force. This article aims to analyze the juridical review of the execution process in land dispute resolution in Indonesia, including the obstacles often encountered in the field, as observed in various regions in Indonesia, particularly in Polewali Mandar Regency. This study employs a normative juridical method with a legislative approach and case studies of court decisions. The research findings show that land dispute executions are frequently hindered by non-juridical factors such as third-party resistance, social conflicts, and political intervention. From a legal perspective, provisions in the HIR, RBg, and the 1960 UUPA serve as the normative foundation for execution. In conclusion, the execution process requires strengthened regulations and synergy between the judiciary, law enforcement agencies, and local governments to ensure legal certainty." Keywords: execution, land disputes, juridical review, legal certainty